ALOE VERA GROWTH WITH ZEOLITE AND ORGANIC MATTER APPLICATION - Azlina Heryati Bakrie (Jurnal Zeolit Indonesia, 2004)
The objective of this study was to evaluate the crop growth of aloe vera by zeolite and organic matters application. This study was conducted in Natar, Lampung Selatan. Treatments were arranged by factorial (5x3) in Randomized Complete Block Design with three replications. First factor were five dosage of zeolit as 0; 75; 150; 225; and 300 kg ha-1. Second factor were three different type of organic matters as: without organic matter, chiken manure, and cow manure. The result showed that zeolite application produced maximum responses for the plant height, petiole leaf fresh weight, thickness of petiole leaf, and root dry weight. Organic matters application could increase plant height, thickness of petiole leaf, petiole leaf fresh weight, and root dry weight. The best responses could produce by chicken manure application. The application of zeolite affected by organic matters on length of leaf and fresh weight of petiole leaf.